사이클론 선회류 약화기 구조에 따른 미세먼지 집진효율 연구 - 정동균(Dong Gyun Jeong); 김범석(Beom Seok Kim); 홍민선(Min Sun Hong) (Daehan hwan'gyeong gonghag hoeji, 2017)
The effect of vortex finder confiqurations on the PM-10 collection efficiencies has been investigated using 7 different types of cyclones. Cyclone inlet velocities were calculated by computational fluid dynamics analysis and PM-10 collection efficiencies were measured from experimental apparatus. The inlet velocities of normal, P and A type cyclones were calculated 15.48 m/sec, 16.03 m/sec and 15.9 m/sec, respectively while experimental results show that PM-10 collection efficiencies were increased 4% for P type and 7% for A type cyclones compared to normal cyclone. Also it was found that there exist optimum parallel head lengths for both P and A type cyclones to maximize the PM-10 collection efficiencies. 선회류 약화기(vortex finder)의 구조와 치수를 변형한 7종류의 cyclone을 제작해 PM-10 집진효율 자료를 도출하였고 CFD 분석을 통한 사이클론 입구 속도를 계산하였다. 입구속도는 normal, P, A type 사이클론의 경우 15.48 m/sec, 16.03 m/sec 그리고 15.90 m/sec로 계산되었고 PM-10 집진효율 실험결과는 P tpye과 A type의 사이클론의 경우 normal 사이클론에 비해 4%와 7%의 집진효율이 증가하였다. 또한 평행부의 길이가 증가함에 따라 PM-10의 집진효율은 증가하다 감소하여 집진효율을 최대화 할 수 있는 길이가 존재함을 보여주었다.